(untitled) (CAHIERS MAGELLANES-NS, 2024)
Background: Stroke, or cerebrovascular accident (CVA), is a major public health problem as a leading cause of disability and death worldwide. Although stroke symptoms and risk factors are prevalent, many populations, such as Saudi Arabia, remain poorly aware of these. Time and better outcomes depend on recognizing the signs of a stroke. The objective of this study was to assess knowledge and stroke warning sign and symptom awareness among Saudi population. Methods: In this cross-sectional study, we conducted a study using structured questionnaire by surveying Saudi adults aged 20 years and older from July to November 2024. With convenience sampling, 1,139 participants were recruited across various regions. We run data analysis using SPSS (version 25) with a confidence level of 95%. Results: Participants were aged 35.5±10.8 years, and 57% were female, 92.4% were of Saudi nationality. On hearing of stroke, a majority had heard of its term (95.7%) but only 56.5% could give an alternative term. However, awareness of other vital risk factors was low; 85.9% recognized hypertension as a primary risk factor. High knowledge levels were observed only in only 26.1% of participants who were also classified as low knowledge about stroke in 36% of them. Stroke symptoms were known by, 73.4% recognized trouble speaking and 31% recognized continued left shoulder pain as symptom. Importantly, however, 43.1% of respondents were unaware of current treatment options though 90.2% agreed that stroke is a medical emergency. Conclusion: This study revealed how the Saudi population has a high level of awareness of the foundations of stroke. Most of participants understood the term 'stroke,' only 26.1% demonstrated high knowledge about its characteristics and risks. A majority answered key symptoms, such as sudden numbness and speech difficulties, correctly, but misconceptions about onset of symptoms and treatment awareness remain of concern Gaps in addressing these should improve timely intervention and potentially decrease stroke related morbidity and mortality in Saudi Arabia.